Killer Elite - McKendry, Gary; Statham, Jason, 1967-; Owen, Clive; De Niro, Robert (Universal City, CA : Universal Studios Home Entertainment, 2012)
Danny, an assassin, retires to the outback, but when his former partner is kidnapped, Danny is forced to take on a group of retired SAS soldiers.
Inspired by the book "The feather men" by Ranulph Fiennes.
Originally released as a motion picture in 2011.
Features: deleted scenes.
Camera, Simon Duggan ; editor, John Gilbert ; music, Johnny Klimek, Reinhold Heil ; production designer, Michelle McGahey.
Jason Statham, Clive Owen, Robert De Niro, Dominic Purcell, Aden Young, Yvonne Strahovski, Ben Mendelsohn, Rodney Afif.
MPAA rating: R.
Keywords: Fiennes, Ranulph, -- Sir, -- 1944- -- Film adaptations; Assassins -- Drama; Great Britain -- Army. -- Special Air Service -- Drama; Action and adventure films; Video recordings for the hearing impaired; Fiction films; Based on the book; Feature films